Experimental and quantum chemical investigations on the oxidative stability of sesame oil base stock with synthetic antioxidant additives. (24th September 2018) - Sabarinath, Sankaran Nair; Prabhakaran Nair, Kumarapillai; Rajendrakumar, Perikinalil Krishnan
Abstract: Depleting resources and increasing environmental pollution caused by the petroleum products made researchers to think about its biodegradable counterparts. Vegetable oils due to its characteristics such as availability, renewability, eco‐friendliness, and biodegradability are progressively encouraged as a replacement for mineral oils in lubricant industry, while enhancement of few properties like the oxidative stability aids in the efficient use of them as the base stock. A generous amount of unsaturation in vegetable oils decreases oxidative stability and improves the pour point. Hence, a compromise between these two properties (pour point and oxidative stability) is critical in vegetable oil‐based lubricant. In this regard, sesame oil (SESO) possesses high pour point, and presence of natural antioxidants in it imparts superior oxidative stability than any other vegetable oils with a higher level of unsaturation. The addition of certain synthetic antioxidants to the SESO helps in the further improvisation of its oxidative stability to suit it for lubricant purpose. In the present work, the oxidative stability of SESO blended with octyl gallate (OG), salicyl hydroxamic acid, 2, 5‐di‐tert‐butyl hydroquinone (DTBHQ), and tertbutyl hydroquinone (TBHQ) are assessed using hot oil oxidation test (HOOT) and differential scanning calorimetry (DSC, ASTM E2009‐08). The results are further compared with commercially available mineral oil‐based lubricant, SAE20W40. HOOT results show that a blend of SESO + 1.5%DTBHQ + 0.5%OG possesses higher oxidative stability than other antioxidant blends with SESO. In addition, from the DSC results, it is observed that the oxidative onset temperature (OOT) for abovementioned combination (268.10°C) shows an increase of 46.6% than the value of neat SESO (182.79°C) and is nearer to SAE20W40 (277.38°C). Fourier‐transform infrared spectroscopy results show that SESO + 1.5%DTBHQ + 0.5%OG combination subjected to HOOT hampers oxidation and hence increases the oxidative stability. The tribological properties of neat and antioxidant added SESO are studied using a four‐ball tester. Quantum chemical studies are also performed for antioxidant molecules on the basis of bond dissociation energies, ionisation potential, and HOMO‐LUMO energy gap to identify the dominant antioxidant mechanisms.